The welfare effects of ICTs in agricultural markets: A case of selected countries in East Africa - Kamande, Mercyline; Nafula, Nancy (International Food Policy Research Institute, 2016)
The use of mobile ICTs (information and communication technologies) in Africa’s agricultural sector has proven to be an efficient and cost-effective method for sharing and exchanging information more widely. ICTs allow farmers to better access critical information, such as pest and disease reports, weather conditions, and market prices, and improve communications between farmers and extensions workers. This study examines the welfare effects of ICTs on both farmers and traders in Rwanda and Kenya. The study uses a descriptive analysis and a quasi-experimental approach to examine selected ICT portals and their level of use among both farmers and traders. Our results reveal that ICTs have negative welfare effects on farmers. However, all the changes are insignificant at the 95 percent level of confidence, which makes it difficult to make a conclusive decision regarding the effects of ICTs on producer welfare in this region